2009
DOI: 10.1007/s00429-009-0212-x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the fluorescent conjugates of cholera toxin subunit B for multiple retrograde tract tracing in the central nervous system

Abstract: Cholera toxin subunit B (CTB) is a sensitive neuroanatomical tracer that generally transports retrogradely in the nervous system, and has been used extensively in brightfield microscopy. Recently, Alexa Fluor (AF) conjugates of CTB have been made available, which now allows multiple tracing with CTB. In this study, we examined the efficacy of these new AF-CTB conjugates when injected into the brain, and compared the results to our previous experiences using fluorescent 3k dextran amines. To test this, we injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…For example, the BA is the only region of the amygdala that receives robust input from the ventral CA1 area of the hippocampus (Pitkanen et al, 2000). Given that cholera toxin is a selective monosynaptic retrograde tracer (Bruce and Grofova, 1992; Conte et al, 2009), we are confident that the CTb labeling we have observed reflects specific afferent projections of the BA.…”
Section: Discussionmentioning
confidence: 70%
“…For example, the BA is the only region of the amygdala that receives robust input from the ventral CA1 area of the hippocampus (Pitkanen et al, 2000). Given that cholera toxin is a selective monosynaptic retrograde tracer (Bruce and Grofova, 1992; Conte et al, 2009), we are confident that the CTb labeling we have observed reflects specific afferent projections of the BA.…”
Section: Discussionmentioning
confidence: 70%
“…Anatomical tracers have occasionally been reported to preferentially bind to certain projections (Schofield et al 2007; Deng and Rogers 1999) and we cannot completely rule out that the differences in the percentage of double-labeled cells in reuniens compared to the subiculum do not result from biases in the binding of CTB-AF conjugates. Nonetheless, CTB is considered a sensitive retrograde tracer (Conte et al 2009) and enters cells by binding to gangliosides in the cell membrane (Stoeckel 1977; Joseph et al 1978). One advantage of CTB conjugates for collateralization studies is that using the same compound minimizes the variability in the spread, uptake and transport that would result from using multiple tracers in the same animal (Conte et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, CTB is considered a sensitive retrograde tracer (Conte et al 2009) and enters cells by binding to gangliosides in the cell membrane (Stoeckel 1977; Joseph et al 1978). One advantage of CTB conjugates for collateralization studies is that using the same compound minimizes the variability in the spread, uptake and transport that would result from using multiple tracers in the same animal (Conte et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In order to identify lateral entorhinal cortical (LEC) cells with afferent projections to CA3, all rats received bilateral injections of the retrograde tracer cholera toxin subunit B (recombinant) Alexa Fluor 594 (CTB; ThermoFisher Scientific, cat # C22842) (Conte et al, 2009a,b) targeting the CA3 region (Paxinos and Watson, 2007). CTB (500 μg) was reconstituted and diluted to 1% in 50 μl of sterile 0.1 M PBS and stored at −20°C until surgery.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was used to quantify the extent to which the active CA3 ensemble updated across different environments, and if this related to a rat's ability to discriminate between two similar objects. Furthermore, Arc catFISH was combined with retrograde tracing to identify those LEC neurons that project directly to CA3 (Conte et al, 2009a,b; Mesina et al, 2016). Importantly, analysis of the entorhinal cortex was restricted to the lateral area.…”
Section: Introductionmentioning
confidence: 99%